PENTINGNYA MEMELIHARA KEBERSIHAN DAN KEAMANAN LINGKUNGAN SECARAPARTISIPATIF DEMI MENINGKATKAN GOTONG ROYONG DAN KUALITAS HIDUP WARGA - Iskandar, Andi Arifuddin (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
The purpose of this research is to find out how the development of hygiene and security environment in the residential location Hertasning RT. 002/RW. 006, Kelurahan Tidung, Makassar and understand the desire of the entire host and guest housing in keeping and creating a security environment in the cleanliness and location of housing Hertasning RT. 002/RW. 006 in order to materialize soon: Siskemling-System Cluster. Research methods, Counselling and guidance is done by Questioning models (Face to Face Relationship) as well as the analysis of the problem by the method of 5W + 1 H, to analyze the problems in respect of Environmental Hygiene and Security on site Housing Hertasning RT. 002/RW. 006, Kelurahan Tidung, Makassar. The presence of individual awareness and all the citizens are so important in carrying out changes in the security environment and hygiene problems, both to the natural environment as well as the social environment. Therefore the modernization with Siskemling-the clusters involving participation of all citizens in this mutual can take towards a better quality of life, orderly and organised. And as a result, the citizens agree with the existence of this way as an alternative in the community aware of the importance of continuing to improve the clean environment, beautiful and secure (Believer) in participatory community development to the community.